Sintesis selulosa bakteri dari jerami kulit nangka dengan penambahan beberapa konsentrasi sukrosa - Budi Santosa; Lorine Tantalu; Natanael Woleka Sairo (Fakultas Pertanian Universitas Yudharta Pasuruan, 2022)
Introduction: Bacterial cellulose or also called nata is a drink shaped like a gel, white, consisting of cellulose (dietary fiber) made from a liquid medium containing carbohydrates by fermenting using the help of microbes with the name Acetobacter xylinum. The purpose of this study was to obtain the best concentration of sucrose in bacterial cellulose synthesis from jackfruit skin straw. Methods: The experimental design used in this study is a complete randomized design of a single factor, as a factor in the concentration of sucrose consisting of 5 levels namely K1 = 1%, K2 = 1.5%, K3 = 2%, K4 = 2.5% and K5 = 3%. Each treatment is repeated 5 times so that the total sample observed as many as 25 pieces. The observed parameters are the thickness of the nata, the weight of the nata, the total fiber content of the nata and the beginning of the formation of nata. Parameters of nata thickness, weight of nata and total fiber content of nata were observed on the 14th day of fermentation after harvesting nata. The initial parameters of the formation of nata are observed at the beginning of fermentation. Results: The results showed that nata thickness increased at 1%, 1.5% and 2% sucrose concentrations. The highest weight of jackfruit skin straw nata was found in the treatment with 2% sucrose concentration, which was 215.8 grams. The sucrose concentration of 2% resulted in the highest fiber content when compared to other treatments. The initial formation of jackfruit skin straw nata was the fastest at the 2% sucrose concentration treatment, which was 2.2 days. Conclusion: The best bacterial cellulose (nata) of jackfruit skin straw was obtained from the treatment with 2% sucrose concentration.